Competencies, Capabilities and Development Capacity - Mark Avery (Asia Pacific Journal of Health Management)
In leading and managing health, aged and social care organisations and systems professionals need to be able to rely on ongoing effective learning and knowledge attainment. Irrespective of the role, function, experience or practice of individual leaders and managers, such a commitment is about growth and development personally and professionally. The competencies – capabilities – development capacity continuum requires an ongoing commitment....